The role of fiber types in muscle hypertrophy: Implications for loading strategies - Ogborn, D.; Schoenfeld, B. J. (Strength and Conditioning Journal, 2014)
Emerging evidence suggests that type i fibers display a substantial propensity for growth if they are selectively targeted via low-load training. The purpose of this article will be to review the research regarding fiber type-specific hypertrophy and draw evidence-based conclusions as to their implications for program design.